Rehabilitation of Algerian rangelands: effects of Atriplex canescens plantation on biodiversity, soil physico-chemical parameters and soil surface elements - Amghar F.; Forey E.; Langlois E.; Brouri L.; Margerie P. (Efficiency and resilience of forage resources and small ruminant production to cope with global challenges in Mediterranean areas, 2021)
The 20 million hectares that covered the Algerian rangelands were the preferred area for breeding a livestock estimated at 24 million head of which 80% were sheep. Examination of desertification sensitivity and biomass maps showed that more than 55% of rangelands were classified as desertification-sensitive and the average animal load was 5.6 ha/head. To combat desertification and support livestock needs, the HCDS had launched a rehabilitation program through the introduction of a forage plant Atriplex canescens. This study was conducted in the department of Djelfa, on a 947 ha plantation, dealing with 4 age groups (2, 5, 10 and 15 years old). For each age group, 3 parcels were selected. In each parcel, 20 plants were pre-selected. For each foot we measured the height and the 4 cardinal rays. Three individuals per parcel were selected on the basis of their membership of the mean ± SE range over the five measured parameters. Three control shrubs, 9 shrubs per age class, 2,340 soil tests and 2,080 contact points were treated under R 3.5.2. It appeared that in 2 years we saw an improvement in the state of the soil surface, in 10 years we noticed an improvement in the carbon level in the soil as well as the diversity indices tested. For the 15-year-old class, an increase in the total nitrogen rate was underlined with a decrease in diversity indices.
1. Joint meeting of the FAO-CIHEAM Networks on Sheep and Goats (Subnetworks on Nutrition and Production Systems) and on Mediterranean Pastures, 2019/10/23-25, Meknes (Morocco)